Effects of a Combination of Atropine, Metaraminol and Pyridine Aldoxime Methanesulfonate (AMP Therapy) on Normal Human Subjects - Taylor, W. J. Russell (1965)
Four hundred and seventeen medical students at the University of Toronto were used as both subjects and observers in a series of double-blind experiments to determine possible toxic effects following oral ingestion of various combinations of 2 mg. atropine, 10 mg. metaraminol and 1 g. pyridine aldoxime methanesulfonate (P(2)S). Heart rate, blood pressure, pupil diameter, and visual accommodation were measured before and at 20-minute intervals after drug administration for 100 minutes. A visual and memory perceptual test (Mackworth) was performed before and 100 minutes after drug ingestion. No toxic effects were observed following administration of the triple combination of atropine, metaraminol and P(2)S (AMP therapy). The AMP combination might be useful prophylactically for persons facing exposure to organophosphorus anticholinesterase compounds. It must not be considered an adequate substitute for treatment should poisoning occur.